Strategic Budget Planning as a Management Control Tool in Venezuelan Universities (Docentes 2.0 Journal, 2021)
The importance of strategic budget planning and management control lies in the fact that in addition to being part of managerial policies, they constitute a primary support tool. This research aimed to analyze and establish the relationship between strategic budget planning and management control as a tool in University Institutes of the public sector. The methodology used was descriptive, correlational, and field, with a non-experimental transectional design. They made up of a census population of 16 directors from both university institutes, 8 for each. The survey was used as a data collection instrument through a questionnaire of 36 items with four alternatives for Likert-type responses to categorize the dimensions and indicators studied. It applied analysis of variance (ANOVA) was to observe significant differences between the presence of the hands and the sizes learned. The results showed a moderate presence in the different indicators and dimensions, without significant differences (P> 0.05). It is concluded that there are weaknesses in the strategic planning process of the budget. Therefore, the management control of the university institutions, specifically in the internal control dimension of the budget, the audit indicators are not present and the rendering of accounts.
Keywords: Strategic planning; Budget; Control; Management; Venezuelan universities